Brain Metabolite Changes After Anodal Transcranial Direct Current Stimulation in Autism Spectrum Disorder - Auvichayapat, Narong; Patjanasoontorn, Niramol; Phuttharak, Warinthorn; Suphakunpinyo, Chanyut; Keeratitanont, Keattichai; Tunkamnerdthai, Orathai; Aneksan, Benchaporn; Klomjai, Wanalee; Boonphongsathian, Wuttisak; Sinkueakunkit, Akkharawat; Punjaruk, Wiyada; Tiamkao, Somsak; et al. (Frontiers in Molecular Neuroscience, 2020)
OBJECTIVES: The previous researches have evidences that transcranial direct current stimulation (tDCS) can reduce autistic severity without knowing the exact mechanism. Magnetic resonance spectroscopy (MRS) in autistic brain showed low level of brain metabolites in anterior cingulate cortex (ACC), amygdala, left dorsolateral prefrontal cortex (DLPFC). The aim of this study is to test the effect of anodal tDCS at the left DLPFC on the autism treatment evaluation checklist (ATEC) social subscales, correlation between brain metabolite changes in the left DLPFC and ATEC social subscales. Other interesting areas such as ACC, amygdala, and locus coeruleus were also demonstrated. METHODS: Ten autistic patients were given 20 min, 1 mA anodal tDCS over the left DLPFC for 5 consecutive days. Measures of ATEC and concentration of brain metabolites were performed before and immediately after treatment. RESULTS: The results showed significant reduction between pre- and immediately post-treatment in ATEC social subscales, significant increases in NAA/Cr and ml/Cr, decrease in Cho/Cr concentration in the left DLPFC and locus coeruleus after tDCS treatment. The significant association between ATEC social subscale decreasing and NAA/Cr, Cho/Cr, and ml/Cr concentration changed in locus coeruleus were positive. CONCLUSIONS: The possibilities of these findings suggest the beneficial effects of tDCS on autism may be due to the changes in neuronal, glia cell activity, and synaptogenesis in the autistic brain network. Additional study with larger sample sizes and a control group is warranted.